HUBUNGAN TINGKAT KEPATUHAN KONSUMSI OBAT ANTI MALARIA TERHADAP KEJADIAN MALARIA PADA IBU HAMIL - Abimulyani, Yumi; Yogi, Ruth; Kainde, Yuliana Yacinta; Mansyur, Tri Novianty; Siregar, Neny San Agustina (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
Malaria poses a significant public health challenge globally, affecting regions with tropical and sub-tropical climates. Malaria can attack people of all ages and genders, including pregnant women. Malaria during pregnancy significantly affects the health of both the mother and the fetus, leading to increased morbidity and mortality rates. The study aimed to determine the relationship between the level of compliance with the consumption of anti-malarial drugs through the periodic malaria prevention program during pregnancy (PEMILA-OAM) in reducing the incidence of malaria in pregnant women. This study employs quantitative methodologies with a retrospective approach. The research sample consisted of 281 pregnant women who were selected by selecting samples using saturated samples. Collecting data using medical records on pregnant women who received the PEMILA-OAM program who gave birth from October 2022 to March 2023. The independent variable was the level of compliance with the consumption of anti-malarial drugs and the dependent variable was the incidence of malaria in pregnant women. Chi-Square test was employed for data analysis, p-value of 0.000 in indicating statistical significance as it was less that the α-value of 0.05. Additionally, the odds ratio (OR) was calculated to be 23.899. It can be concluded that there was significant influence on the level of compliance with the consumption of antimalarial drugs through the malaria prevention program during pregnancy (PEMILA-OAM) in reducing the incidence of malaria in pregnant women and reducing the risk of malaria incidence by 23x compared to pregnant women who do not participate in the PEMILA-OAM program regularly.